Amoebic liver abscess in the medical emergency of a North Indian hospital - Sharma, Navneet (BioMed Central, 2010)
BACKGROUND: Amoebic Liver abscess although fairly common in developing countries, yet, there is limited data on the clinical presentation to the emergency department. A retrospective analysis of 86 indoor cases of Amoebic Liver Abscess presenting to the emergency department over a 5-year period was carried out. FINDINGS: The mean age of patients was 40.5 ± 2.1 years (male-female ratio = 7:1). Fever, pain abdomen and diarrhea were seen in 94%, 90% and 10.5% respectively. Duration of symptoms less than 2 weeks was seen in 48% cases. Hepatomegaly was present in 16% cases only, a right sided pleural effusion in 14% cases and ascites in 5.7%. On ultrasound, a right lobe abscess was seen in 65%, a left lobe abscess in 13% and multiple abscesses in both the lobes in 22% cases. Seventy one cases underwent per-cutaneous pigtail catheter drainage for a mean period of 13.4 ± 0.8 days. The mortality rate was 5.8%. On multivariate regression and correlation analysis, a higher number of inserted pigtail catheters correlated to mortality. CONCLUSIONS: Amoebic liver abscess presents commonly to the emergency department and should be suspected in persons with prolonged fever and pain abdomen. Conservative management for uncomplicated amoebic liver abscess and insertion of single per-cutaneous pigtail catheter drainage for complicated amoebic liver abscess are efficacious as treatment modalities.